Tibial Tubercle Trochlear Groove Distance Does Not Correlate With Patellar Tendon Length in Patients Who Underwent Anterior Cruciate Ligament Reconstruction - Emma E. Johnson, M.D; William L. Johns, M.D; Bryson Kemler, M.D; Rahul Muchintala, B.S; Ryan W. Paul, B.S; Manoj Reddy, M.D; Brandon J. Erickson, M.D (Elsevier, 2024)
Purpose: To examine the relationship between tibial tubercle-trochlear groove (TT-TG) distance and patellar tendon length. Methods: All healthy athletes who underwent anterior cruciate ligament reconstruction who had a magnetic resonance imaging (MRI) study of the knee on file between July 2018 and June 2019 at a single institution were retrospectively reviewed. Exclusion criteria included patients without an MRI study of the knee on file or with an MRI of insufficient quality precluding reliable calculation of TT-TG and patellar tendon length. MRIs were reviewed to calculate TT-TG, patellar tendon length, and Caton-Deschamps Index (CDI). Patient charts were reviewed to obtain anthropometric characteristics including sex, concomitant injuries, and previous knee procedures as well as age at time of MRI. Spearman correlations were used to assess the relationship between TT-TG, patellar tendon length, and CDI, with regression analysis performed to assess for relationships between TT-TG, patellar tendon length, and patient-specific factors. Results: Overall, 235 patients (99 female [42.1%], 136 male [57.9%]; mean age: 30.0 years [23.0; 40.0]) were included. Inter-rater reliability between the 2 reviewers was 0.888 for TT-TG, 0.804 for patellar tendon length, and 0.748 for CDI, indicating strong agreement. The correlation between TT-TG and patellar tendon length was 0.021, indicating no true relationship. The correlation between TT-TG and CDI was -0.048 and that of patellar tendon length and CDI was 0.411, indicating a weak positive relationship. Regression analysis found that male sex is strongly correlated with a longer patellar tendon length (odds ratio 2.65, 95% confidence interval 1.33-3.97, P < .001). Conclusions: In this study, no correlation was found between TT-TG and patellar tendon length or CDI. Male sex was correlated with a longer patellar length. Clinical Relevance: TT-TG does not appear to be a useful preoperative indicator of patellar tendon length and likely does not hold substantial value in preoperative templating of BTB graft sizes.